A practical guide to invasive neurophysiology in patients with deep brain stimulation. (August 2022) - Neumann, Wolf-Julian; Köhler, Richard M.; Kühn, Andrea A.
Highlights: The relevance of invasive neurophysiology in DBS patients is described. Practical aspects of DBS recordings are introduced. An outlook on the future of DBS neurophysiology is provided. Abstract: Deep brain stimulation (DBS) offers the unique opportunity to record human neural population activity as multiunit activity and local field potentials (LFP) directly from the target area in the depth of the brain. This has led to important discoveries through characterization of pathological activity patterns and identification of motor and cognitive correlates of basal ganglia function in patients with movement disorders. These findings have been covered extensively in a large body of literature, but the technical aspects of microelectrode and LFP recordings in DBS patients are rarely reported. This review summarizes the experience from invasive neurophysiology experiments in over 500 DBS cases in the last 20 years in a single centre. It introduces the basics of intraoperative microelectrode recordings, discusses the neurophysiological and technical aspects of LFP signals and gives and outlook on current and next-generation developments - from sensing enabled implantable devices to combined electrocorticography and LFP recordings during adaptive DBS.